Evolution of microstructures on silicon induced by femtosecond laser with multiple pulses - Yuan, D.Q.; Zhou, M.; Lu, D.Q.; Xu, J.T. (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The effect of multiple pulses of Ti:sapphire femtosecond laser system on silicon wafer was investigated. Using the pulse energy exceed the threshold of silicon to investigate the evolvement of structures and found that exceed certain fluence no any periodic structure will appearance. For 1.91 J/cm2, the pattern of columnar structure was formed in the central region of irradiation area. In further experiment, using the subthreshold multiple pulse femtosecond laser irradiation of 0.91 J/cm2, the periodic ripple structures and nanohole array were presented in the whole irradiation area due to the incubation effection. Also, we obtained the threshold of nanohole array to be higher than that of the periodic ripple structures.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 727-734
Keywords: optyka; femtosecond laser; evolvement; ripples; subthreshold; silicon